2014
DOI: 10.1002/hbm.22530
|View full text |Cite
|
Sign up to set email alerts
|

Feeling safe in the plane: Neural mechanisms underlying superior action control in airplane pilot trainees—A combined EEG/MRS study

Abstract: In day-to-day life, we need to apply strategies to cascade different actions for efficient unfolding of behaviour. While deficits in action cascading are examined extensively, almost nothing is known about the neuronal mechanisms mediating superior performance above the normal level. To examine this question, we investigate action control in airplane pilot trainees. We use a stop-change paradigm that is able to estimate the efficiency of action cascading on the basis of mathematical constraints. Behavioural an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
62
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 33 publications
(65 reference statements)
7
62
1
Order By: Relevance
“…So far, very little is known about the neuromodulation of action cascading, although there is evidence showing that dopaminergic and the gamma-aminobutyric acid (GABA)-ergic system are important (Stock et al, 2014a(Stock et al, , 2014bBeste and Saft, 2013). Concerning the GABA-ergic system, recent findings using magnetic resonance spectroscopy (MRS) showed that superior performance in action cascading was associated with increased concentrations of striatal GABA (Yildiz et al, 2014a). Given the correlational nature of MRS studies, it is, however, hard to infer the exact role of GABA in mediating action cascading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, very little is known about the neuromodulation of action cascading, although there is evidence showing that dopaminergic and the gamma-aminobutyric acid (GABA)-ergic system are important (Stock et al, 2014a(Stock et al, , 2014bBeste and Saft, 2013). Concerning the GABA-ergic system, recent findings using magnetic resonance spectroscopy (MRS) showed that superior performance in action cascading was associated with increased concentrations of striatal GABA (Yildiz et al, 2014a). Given the correlational nature of MRS studies, it is, however, hard to infer the exact role of GABA in mediating action cascading.…”
Section: Introductionmentioning
confidence: 99%
“…We assessed action cascading by means of a wellestablished stop-change paradigm (Verbruggen et al, 2008), in which we varied the interval between "stopping" and "changing" (stop-change delay; SCD) and hence varied the time available for preparation before executing the change response (Mückschel et al, 2014). Given the idea that GABA and NE impact action selection (Yildiz et al, 2014a;Yildiz et al, 2014b), we expected the active tVNS to ameliorate the action cascading processes (i.e. decrease reaction times on the change stimuli) when (i) an interruption, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we examined to what extent the neural dynamics in the rIFG, as modulated via iTBS or cTBS, are related to the inferred strategy and efficiency of multi-component behaviour. Moreover, by recorded event-related potentials (ERPs), we were able to identify associated alterations in cognitive processes on the attentional and response selection levels, both of which may contribute to shifts in multi-component processing strategies 1,14,15 . cTBS applied to the rIFG results in a less efficient action cascading strategy, whereas iTBS results in a more efficient strategy, compared with a shamTBS control condition.…”
mentioning
confidence: 99%
“…Consistent with this hypothesis, Yildiz et al (2014) have shown by magnetic resonance spectroscopy (MRS) that superior performance of cascade action was associated with increased striatal GABA concentrations [98]. Another point, the active transcutaneous stimulation of the vagus nerve (tVNS) which increases the concentration of GABA and norepinephrine (NE), improved functions of response selection during the cascade action, compared with the stimulus simulation [99]. These results suggest a critical role of GABA in the neuromodulation of cascade action processes.…”
Section: Gabamentioning
confidence: 95%
“…These results suggest a critical role of GABA in the neuromodulation of cascade action processes. They also suggest that the increase [98,99] not too high [100] of GABA levels are associated with better performance of these cascade actions. In another study, Steenbergen et al (2015b) aimed to provide converged and direct evidence about the possible key role of the GABAergic system in modulating the efficacy of cascade action [101].…”
Section: Gabamentioning
confidence: 97%